2022
DOI: 10.22146/jh.65058
|View full text |Cite
|
Sign up to set email alerts
|

Javanese Politeness Experience as Depicted in Its Speech Levels of the Transactional Communication

Abstract: Javanese interactions are bound by politeness speech levels. Ngoko, the lowest form, reflects the interactions between close equals, or persons of higher status towards those of lower status, whereas krama, the highest form, is used to address elders or those of higher status. This study aimed to disclose communication politeness as expressed by Javanese users in the public place. Twelve participants were enlisted, among them seven males and five females. Data were recorded from a smartphone and transcribed or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…96 In addition, Didik Rinan Sumekto, et al convey that politeness attempts to formulate a system that facilitates and maintains users' interaction through minimal potential conflicts and confrontations to adhere to harmonious relations. 97 Further, Dena Agustina et al summarize that the implementation of local traditions in a community can significantly contribute to the development of religious values and the pluralistic society of Indonesia. 98 According to Mita Purbasari Wahidiyat, et al stress that the changes in some aspects of ideology (ideology of development, religion, and market) were controlled by the main ideology, called the authority of ideology.…”
Section: Destructive Provocationsmentioning
confidence: 99%
“…96 In addition, Didik Rinan Sumekto, et al convey that politeness attempts to formulate a system that facilitates and maintains users' interaction through minimal potential conflicts and confrontations to adhere to harmonious relations. 97 Further, Dena Agustina et al summarize that the implementation of local traditions in a community can significantly contribute to the development of religious values and the pluralistic society of Indonesia. 98 According to Mita Purbasari Wahidiyat, et al stress that the changes in some aspects of ideology (ideology of development, religion, and market) were controlled by the main ideology, called the authority of ideology.…”
Section: Destructive Provocationsmentioning
confidence: 99%
“…From a microlinguistic perspective, Krauße (2018) and Atmawati (2021) showed that politeness, honorific, and deferential systems are embedded in the Javanese vocabularies. Meanwhile, studies on politeness in various speech events reveal that by considering the context of situation, Javanese speakers actively adjust their words and expressions to convey politeness to show respect or intimacy, such as refusal strategies used by Javanese learners of English (Wijayanto, 2013), politeness strategies in Javanese political discourse (Santoso, 2015), strategies and levels of politeness in tourism-service language (Purnomo, 2016), and Javanese speech levels in transactional communication (Sumekto et al, 2022). Studies that compared the politeness of Javanese and other languages, such as Tiarawati and Wulandari (2015), Kuntarto (2018), Sugianto (2021), andNurjaleka et al (2022), strengthen the argument that politeness is culturally distinctive, even between languages with similar politeness systems.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia, one of the Asia countries, is renowned for having a variety of cultures, such as Minang, Malay, Batak, Betawi, Dayak, and Java. SBY and Jokowi, who are Javanese, always apply the concept of politeness in delivering their state speeches (Sumekto et al, 2022), including when addressing their inaugural speeches as president (Laksana, 2021). Although SBY and Jokowi are both Javanese, some fundamental differences are observed in macroand micro-linguistics.…”
Section: Introductionmentioning
confidence: 99%